Efficacy of the Children in Disaster: Evaluation and Recovery (CIDER) Protocol for Traumatized Adolescents in Korea - Lee, Mi-Sun; Kim, Hyun Soo; Park, Eun Jin; Bhang, Soo-Young (Journal of Korean medical science, 2020)
We aimed to evaluate the feasibility of trauma-focused group therapy in adolescents exposed to traumatic events in Korea.BACKGROUNDWe aimed to evaluate the feasibility of trauma-focused group therapy in adolescents exposed to traumatic events in Korea.We recruited 22 adolescents (mean age, 16 years; standard deviation, 1.43; range, 13-18 years). Children in Disaster: Evaluation and Recovery (CIDER) V1.0 is a trauma-focused group therapy comprising eight 50-minute-long sessions. The effectiveness of the intervention was evaluated using the Korean version of the Children's Response to Traumatic Events Scale-Revised (K-CRTES-R), the Beck Depression Inventory (BDI), the State Anxiety Inventory for Children (SAIC), and the Pediatric Quality of Life Inventory (PedsQL). The data were analyzed by the Wilcoxon signed-rank test.METHODSWe recruited 22 adolescents (mean age, 16 years; standard deviation, 1.43; range, 13-18 years). Children in Disaster: Evaluation and Recovery (CIDER) V1.0 is a trauma-focused group therapy comprising eight 50-minute-long sessions. The effectiveness of the intervention was evaluated using the Korean version of the Children's Response to Traumatic Events Scale-Revised (K-CRTES-R), the Beck Depression Inventory (BDI), the State Anxiety Inventory for Children (SAIC), and the Pediatric Quality of Life Inventory (PedsQL). The data were analyzed by the Wilcoxon signed-rank test.A significant improvement was revealed in trauma-related symptom scores (Z = -2.85, P < 0.01), depressive symptom scores (Z = -2.35, P < 0.05) and quality of life scores (Z = -3.08, P < 0.01). Additionally, a marginally significant improvement was found in anxiety symptom scores (Z = -1.90, P = 0.058).RESULTSA significant improvement was revealed in trauma-related symptom scores (Z = -2.85, P < 0.01), depressive symptom scores (Z = -2.35, P < 0.05) and quality of life scores (Z = -3.08, P < 0.01). Additionally, a marginally significant improvement was found in anxiety symptom scores (Z = -1.90, P = 0.058).CIDER is a potentially effective intervention for adolescents exposed to traumatic events. Larger controlled trials are needed.CONCLUSIONCIDER is a potentially effective intervention for adolescents exposed to traumatic events. Larger controlled trials are needed.Clinical Research Information Service Identifier: KCT0004681.TRIAL REGISTRATIONClinical Research Information Service Identifier: KCT0004681.